The gun-shot woundings of large bowel as a predictor of severe course of fighting abdominal trauma - І. A. Lurin; K. V. Gumeniuk; O. B. Tymchuk; O. M. Popova (Клінічна хірургія, 2021)
Objective. Analysis of experience of the medical help delivery to the wounded persons, suffering a gun-shot fighting abdominal trauma and treated in Military–Medical Clinical Centre of Eastern Region, determining a further steps, concerning optimization of the treatment-diagnosis measures in this category of patients.